Remembering the "Forgotten Zone": Recasting the Image of the Post-1945 French Occupation of Germany. Issue 3 (1st December 2019) - Campion, Corey
Abstract : In much of the English-language scholarship on the post-1945 Allied occupation of Germany, French officials appear as little more than late arrivals to the victors' table, in need of and destined to follow Anglo-American leadership in the emerging Cold War. However, French occupation policies were unique within the western camp and helped lay the foundations of postwar Franco-German reconciliation that are often credited to the 1963 Elysée Treaty. Exploring how the French occupation has been neglected, this article traces the memory of the zone across the often-disconnected work of French-, German-, and English-speaking scholars since the 1950s. Moreover, it outlines new avenues of research that could help historians resurrect the unique experience of the French zone and enrich our appreciation of the Franco-German "motor" on which Europe still relies.